Antecedents of organizational commitment among faculty: an exploratory study. Issue 2 (2nd April 2016) - Lovakov, Andrey
Abstract : Faculty are the main asset of a university and determine its success. The attitudes of faculty toward their institution play an especially important role in the academic profession. This study examines the specific antecedents of affective, normative and continuance commitment of faculty to their university. This study is an online survey of 317 faculty of Russian higher education institutions. The results of the regression analysis showed that being an undergraduate inbred (i.e. working at the university from which one graduated) predicted affective and normative commitment toward the university, while having a post at another higher education institution predicted only affective commitment. Faculty who work at several universities have lower levels of emotional attachment to the primary university.